Historical review and redescription of three poorly known species of the catfish genus Trichomycterus from south-eastern Brazil (Siluriformes: Trichomycteridae). Issue 47 (25th December 2019) - Costa, Wilson J. E. M.; Katz, Axel M.; Mattos, José Leonardo O.; Amorim, Pedro F.; Mesquita, Beatrizz O.; Vilardo, Paulo J.; Barbosa, Maria Anais
ABSTRACT: This study is primarily directed to the most poorly known species of the genus Trichomycterus, comprising five nominal species ( T. florensis, T. immaculatus, T. nigricans, T. paquequerensis and T. santaeritae ) endemic to south-eastern Brazil. One of them, T. nigricans, is the type species of the genus, involved in taxonomic problems for over 150 years. A detailed historical review, accompanied by examination of type specimens and recent collections, revealed that the correct type locality of T. nigricans is in the vicinity of Rio de Janeiro, not Santa Catarina as commonly appears in the literature; specimens previously misidentified as T. nigricans from Santa Catarina belong to a possibly undescribed species of the genus Cambeva ; T. paquequerensis is a synonym of T. immaculatus, and T. florensis is a synonym of T. santaeritae ; and the hypothesis that T. santaeritae is closely related to the Amazon Sarcoglanidinae is refuted. The three valid species are redescribed. These species are members of a clade also including T. caipora that is highly supported by molecular data, diagnosed by a pronounced posterior maxillary process and caudal fin emarginate at least in larger specimens. A subclade comprising T. caipora, T. nigricans and T. santaeritae is diagnosed by a long maxilla and a bifid anterior extremity of hypobranchial 3.